2017
DOI: 10.1371/journal.pone.0171705
|View full text |Cite
|
Sign up to set email alerts
|

How does the cladoceran Daphnia pulex affect the fate of Escherichia coli in water?

Abstract: The faecal indicator Escherichia coli plays a central role in water quality assessment and monitoring. It is therefore essential to understand its fate under various environmental constraints such as predation by bacterivorous zooplankton. Whereas most studies have examined how protozooplankton communities (heterotrophic nanoflagellates and ciliates) affect the fate of E. coli in water, the capacity of metazooplankton to control the faecal indicator remains poorly understood. In this study, we investigated how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 56 publications
(72 reference statements)
2
21
0
Order By: Relevance
“…These approaches with chemically altered bacteria or beads may impact the feeding rate and do not consider inactivation, which is important when considering water quality implications. A recent study investigated the impact of bacterial concentration and daphnid density on the ingestion and inactivation of E. coli by Daphnia pulex using culture-based techniques (10). The observed trends and calculated uptake rates were different than those observed herein and could not be directly compared due to the different methodology and species used.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…These approaches with chemically altered bacteria or beads may impact the feeding rate and do not consider inactivation, which is important when considering water quality implications. A recent study investigated the impact of bacterial concentration and daphnid density on the ingestion and inactivation of E. coli by Daphnia pulex using culture-based techniques (10). The observed trends and calculated uptake rates were different than those observed herein and could not be directly compared due to the different methodology and species used.…”
Section: Resultsmentioning
confidence: 64%
“…In addition, the lack of particles may result in reduced filtration rates, since fewer particles are encountered during grazing. Previous studies examining DAPI (4=,6-diamidino-2-phenylindole)-labeled E. coli cells fed to D. pulex showed that E. coli was contained within the food boluses of D. pulex, and uptake was observed within minutes of exposure (10). These studies also showed passage of E. coli cells within the gut, but DAPI stain could not be used to indicate viability (10).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S2). Standard curves were constructed using genomic DNA from a pure culture of E. coli (~10 7 CFU mL À1 ) as described earlier (Burnet et al, 2017). Genomic DNA was then serially log-diluted in DNase-free water.…”
Section: Enumeration Of E Coli By Real-time Pcrmentioning
confidence: 99%